Vapor-Phase Hydrogenation of Levulinic Acid to γ-Valerolactone Over Bi-Functional Ni/HZSM-5 Catalyst - Popova, Margarita; Djinović, Petar; Ristić, Alenka; Lazarova, Hristina; Dražić, Goran; Pintar, Albin; Balu, Alina M.; Novak Tušar, Nataša (Frontiers in Chemistry, 2018)
The hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) in vapor-phase is economically more viable route if compared to reaction in liquid-phase. To improve the GVL yield in the vapor-phase reaction, the optimization of nickel modified zeolite as bi-functional catalyst (Ni/HZSM-5) was studied. Ni/HZSM-5 materials with fixed Al/Si molar ratio of 0.04 and different nominal Ni/Si molar ratios (from 0.01 to 0.05) were synthesized without the use of organic template and with the most affordable sources of silica and alumina. Materials were characterized by X-ray powder diffraction, SEM-EDX, TEM-EDX, pyridine TPD and DRIFTS, H2-TPR, N2 physisorption and isoelectric point. In the synthesized materials, 61-83 % of nickel is present as bulk NiO and increases with nickel content. Additionally, in all catalysts, a small fraction of Ni2+ which strongly interacts with the zeolite support was detected (10-18 %), as well as Ni2+ acting as charge compensating cations for Brønsted acid sites (7-21 %). Increasing the nickel content in the catalysts leads to a progressive decrease of Brønsted acid sites (BAS) and concomitant increase of Lewis acid sites (LAS). When BAS/LAS is approaching to 1 and at the same time the amount of NiO reducible active sites is around 80%, the bi-functional Ni/HZSM-5-3 catalyst (Ni/Al = 0.59) leads to 99 % conversion of LA and 100 % selectivity to GVL at 320 oC. This catalyst also shows stable levulinic acid hydrogenation to GVL in 3 reaction cycles conducted at 320 oC. The concerted action of the following active sites in the catalyst is a key element for its optimized performance: 1) Ni metallic active sites with hydrogenation effect, 2) Lewis acid sites with dehydration effect and 3) nickel aluminate sites with synergetic and stabilising effects of all active sites in the catalyst.